Knowledge regarding prevention of hypothermia in newborns among mothers in Northern India - Qazi, Mahvish; Saqib, Najmus; Raina, Rohit (International Journal of Research in Medical Sciences, 2019)
Background: Neonatal hypothermia is increasingly recognized as a risk factor for newborn survival. World Health Organization (WHO) recommends maintaining a warm chain and skin-to-skin care for thermo-protection of newborn children. Since little is known about practices related to newborn hypothermia, this study’s goal was to assess the knowledge of mothers of newborns especially LBW babies on prevention of hypothermia and to provide them the knowledge of cost-effective thermal protection measures. Methods: It was a cross-sectional study using pre-tested, pre-structured questionnaire. 108 postnatal mothers having LBW babies admitted in postnatal wards of Government Medical College, Jammu, Jammu and Kashmir, India were included in the study and analysed using SPSS version 20. Results: Out of 108 mothers, maximum mothers were of age less than 25 years (51%), 60% were from rural area, residing in nuclear family were 62%. Mothers attended hospital for confinement were 95% and 85% started breast feeding their babies. 45% had knowledge of keeping the baby warm by immediately wiping the baby and only 3% mothers had knowledge of Kangaroo Mother Care (KMC). Conclusions: Understanding and addressing community-based practices on hypothermia, prevention and management might help to improve newborn survival in resource-limited settings. Possible interventions include the implementation of skin-to-skin care in rural areas and the use of appropriate, low-cost newborn warmers to prevent hypothermia and support families in their provision of newborn thermal protection. Training family members to support mothers in the provision of thermo-protection for their newborns could facilitate these practices. Those who fail to fully attend antenatal clinics should be targeted for newborn care education.